Profile of Research Skills in the Integrated Guided Inquiry Model Research Skill Development (RSD) Framework - Neni Nuryani; Jujun Ratnasari; Sistiana Windyariani (Quagga: Jurnal Pendidikan dan Biologi, 2024)
Research skills are one of the skills that exist in educational goals, research skills must be possessed to be able to face the 21st century. Research skills of students in Indonesia are still in the low category, this is evidenced by research that has been conducted by previous researchers with an average score -average 68.5 out of 100 points. This study aims to determine the research skill profile of students in one of the MAN schools in Sukabumi City. This study used a descriptive method, the subjects in this study were class XI students, totaling 22 students, determined by a sampling technique, namely purposive sampling. The instruments used were an attitude scale for research skills, and a Research Skill Development (RSD) assessment rubric. The results showed that students' research skill profiles were in the good category with an average score on the attitude scale of 83 ± 6.2% and on the practicum report 71 ± 8.5%. Therefore, it can be seen that the research skills profile of students using the guided inquiry learning model integrated with the Research Skill Development (RSD) Framework in this study is in the good category.